A progressão multi-sistêmica do transtorno bipolar: dos fatores de risco à intervenção - Leclerc, Emilie [UNIFESP] (2018)
Objective: Comprehensively review studies evaluating factors associated with adherence to treatment in bipolar disorder (BD), as well as the results of interventions developed to enhance adherence in this population. Methods: The following search engines were consulted: PubMed, Scielo, LILACS and PsycINFO. The keywords used were ‘‘Bipolar Disorder’’, ‘‘Factor’’, ‘‘Adherence’’, ‘‘Nonadherence’’, ‘‘Compliance’’ and ‘‘Intervention’’. In addition, references list of selected studies were consulted searching for relevant articles. Results: Adherence has been defined in various ways, with some considering adherence vs. nonadherence, and other including a ‘‘partial’’ adherence measure. In addition, methods to assess adherence differ for each study. Several factors were related to poor adherence, including patientrelated factors (e.g. younger age, male gender, low level of education, alcohol and drugs comorbidity), disorderrelated factors (e.g. younger age of onset, severity of BD, insight and lack of awareness of illness) and treatmentrelated factors (e.g. side effects of medications, effectiveness). To improve adherence, the main recommendations are to provide customized interventions focusing on the underlying causes of nonadherence, strong therapeutic alliance and different modalities based on psychoeducation.